2016
DOI: 10.1177/1747954115624823
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different small-sided games on physical and physiological demands in rugby union players

Abstract: This study aimed to describe the influence of four different small-sided games with 15-min duration on physical and physiological demands in rugby union players. Fourteen rugby union players (22.4 AE 3.2 years) participated in the study that was conducted during the competitive period of final-four first Division of 2012-2013 qualifying competition. Timemotion and body impact data were collected using global positional systems technology with heart rate monitored continuously across training sessions. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…A summary of the methods and results of the studies which include the use of GPS in senior and age-grade male RU players is presented in Tables 1 and 2 , respectively. There were a total of 1206 participants included in 34 studies [ 3 , 4 , 6 , 18 , 23 , 26 34 , 39 41 , 43 , 46 48 , 50 53 , 55 , 58 , 62 68 ] utilising GPS and AS in senior male RU players (mean ± SD; age 26.2 ± 1.9 years; height 185.7 ± 2.6 cm; mass: 101.3 ± 4.2 kg). Seventeen of these studies reported the number of data files extracted ( n = 3151).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of the methods and results of the studies which include the use of GPS in senior and age-grade male RU players is presented in Tables 1 and 2 , respectively. There were a total of 1206 participants included in 34 studies [ 3 , 4 , 6 , 18 , 23 , 26 34 , 39 41 , 43 , 46 48 , 50 53 , 55 , 58 , 62 68 ] utilising GPS and AS in senior male RU players (mean ± SD; age 26.2 ± 1.9 years; height 185.7 ± 2.6 cm; mass: 101.3 ± 4.2 kg). Seventeen of these studies reported the number of data files extracted ( n = 3151).…”
Section: Resultsmentioning
confidence: 99%
“… Results showed no significant differences between experience and novice players. Vaz et al [ 41 ] 14 professional rugby union players. GPSports SPI Pro Data were collected from GPS tracking devices (5 Hz) during small-sided games during an in-season competition period.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting finding of this study was that despite the differing constraints applied, the movement demands of the two game form structures examined herevolume and quality -were still relatively similar to each other in terms of both mean and peak demands. Research in rugby 15's and field hockey also documented similar running demands for different small sided training game structures (14,43). Previous research demonstrates that team sports players reduce their levels physical exertion in the periods immediately following the highest intensity periods of play (4,29), suggesting that players regulate their levels of exertion to ensure adequate reserves for future periods of play (44).…”
Section: Discussionmentioning
confidence: 88%
“…13 Limited research is available investigating the effect of constraint manipulation on physical and technical characteristics specifically in rugby football codes SSG and contrasting findings can be found in the literature. 14 For example, in terms of physical characteristics, Kennett, Kempton 15 found higher external and internal loads with greater pitch dimensions, whereas Vaz et al 16 observed no effect of pitch dimensions on external and internal loads in rugby union. Similarly, technical characteristics (e.g., total passes) showed both no difference 17 and an increase 18 when pitch dimensions were reduced in rugby league SSG.…”
Section: Introductionmentioning
confidence: 99%